Oxidative cross-linking of potato proteins by fungal laccases: Reaction kinetics and effects on the structural and functional properties. (July 2021) - Li, Mingqin; Karboune, Salwa; Light, Kelly; Kermasha, Selim
Abstract: Aiming at developing biocatalytic approach to modulate potato proteins functionalities, laccase-catalyzed oxidative cross-linking of potato proteins was investigated in terms of enzyme kinetics, reaction time course and product structural-functional properties. The catalytic efficiency (kcat/Km, mM −1 S −1 ) of fungal laccases in oxidizing patatin-enriched potato protein (PAT, 0.010–0.748) was higher than that of potato protease inhibitors (PIs, 0.008–0.184). While PIs formed more efficiently oxidative cross-linked products. Cross-linking of potato proteins were achieved by laccase alone or by laccase-ferulic acid system; ferulic acid contributed to higher cross-linking extent and to the antioxidant activity of modified proteins. Potato proteins exhibited similar or slightly enhanced solubility upon cross-linking, except that highly cross-linked PIs (cross-linking extent >30%) obtained from Coriolus hirsutus laccase (LacCh)-treatments showed reduced solubility. General improvement in the emulsification property of potato proteins was observed upon cross-linking. Cross-linked potato proteins from LacCh-6 h treatment showed good foaming property; these proteins exhibited enhanced molecular flexibility and the characteristics of mild cross-linking extent (9.6–17.1%) with the accumulation of moderate molecular weight fraction (PAT:60–80 kDa, PIs:30–40 kDa). This study will lay foundations for the exploitation of potato proteins as functional ingredients. Industrial relevance: The exploitation of novel proteins as functional ingredients is needed in order to meet the high demands for natural, healthy-oriented and sustainable food products. Laccase-catalyzed protein cross-linking is a promising green technology for tailoring the functionality of protein ingredients and achieving the desired textural/rheological quality of final products. The current study demonstrated the effectiveness of this enzymatic approach to enhance foaming and emulsifying properties of potato proteins. This approach can be adopted to modulate the functionality of other plant proteins and to develop plant proteins-based functional ingredients for various applications including stable delivery system, fat-replacing biopolymer matrix, meat analog/vegan products and gluten-replacement formulations. Highlights: Kinetics and reaction pathways of laccase-catalyzed cross-linking of potato proteins were elucidated. Laccase-treatments enhanced the emulsification properties of potato proteins. Foaming property can be favored by the use of a short treatment time or mild cross-linking conditions. Composition/structure-functionality relationships of cross-linked proteins were enlightened. The use of ferulic acid mediator can affect the potato proteins modification and their properties.